Retention of knowledge and clinical competence among Ugandan mid-level health providers 1 year after intensive clinical mentorship in TB and HIV management - Dan K. Senjovu; Sarah Naikoba; Pallen Mugabe; Damazo T. Kadengye; Carey McCarthy; Patricia L. Riley; Shona Dalal (BMC, 2021)
Abstract Introduction Clinical mentorship is effective in improving knowledge and competence of health providers and may be a useful task sharing approach for improving antiretroviral therapy. However, the endurance of the effect of clinical mentorship is uncertain. Methods The midlevel health providers who participated in a cluster-randomized trial of one-on-one, on-site, clinical mentorship in tuberculosis and HIV for 8 h a week, every 6 weeks over 9 months were followed to determine if the gains in knowledge and competence that occurred after the intervention were sustained 6- and 12-months post-intervention. In December 2014 and June 2015, their knowledge and clinical competence were respectively assessed using vignettes and a clinical observation tool of patient care. Multilevel mixed effects regression analysis was used to compare the differences in mean scores for knowledge and clinical competence between times 0, 1, 2, and 3 by arm. Results At the end of the intervention phase of the trial, the mean gain in knowledge scores and clinical competence scores in the intervention arm was 13.4% (95% confidence interval ([CI]: 7.2, 19.6), and 27.8% (95% CI: 21.1, 34.5) respectively, with no changes seen in the control arm. Following the end of the intervention; knowledge mean scores in the intervention arm did not significantly decrease at 6 months (0.6% [95% CI − 1.4, 2.6]) or 12 months (− 2.8% [95% CI: − 5.9, 0.3]) while scores in the control arm significantly increased at 6 months (6.6% [95% CI: 4.4, 8.9]) and 12 months (7.9% [95% CI: 5.4, 10.5]). Also, no significant decrease in clinical competence mean scores for intervention arm was seen at 6 month (2.8% [95% CI: − 1.8, 7.5] and 12 months (3.7% [95% CI: − 2.4, 9.8]) while in the control arm, a significant increase was seen at 6 months (5.8% [95% CI: 1.2, 10.3] and 12 months (11.5% [95% CI: 7.6, 15.5]). Conclusions Mentees sustained the competence and knowledge gained after the intervention for a period of one year. Although, there was an increase in knowledge in the control group over the follow-up period, MLP in the intervention arm experienced earlier and sustained gains. One-on-one clinical mentorship should be scaled-up as a task-sharing approach to improve clinical care. Trial Registration The study received ethics approvals from 3 institutions-the US Centers for Disease Control and Prevention Institutional Review Board (USA), the Institutional Review Board "JCRC's HIV/AIDS Research Committee" IRB#1-IRB00001515 with Federal Wide Assurance number (FWA00009772) based in Kampala and the Uganda National Council of Science and Technology (Uganda) which approves all scientific protocols to be implemented in Uganda.